The Novel Induction of Retinal Ganglion Cell Apoptosis in Porcine Organ Culture by NMDA — An Opportunity for the Replacement of Animals in Experiments. Issue 6 (December 2016) - Kuehn, Sandra; Hurst, Jose; Jashari, Adelina; Ahrens, Kathrin; Tsai, Teresa; Wunderlich, Ilan M.; Dick, H. Burkhard; Joachim, Stephanie C.; Schnichels, Sven
Some of the advantages of retina organ culture models include their efficient and easy handling and the ability to standardise relevant parameters. Additionally, when porcine eyes are obtained from the food industry, no animals are killed solely for research purposes. To induce retinal degeneration, a commonly used toxic substance, N -methyl-D-aspartate (NMDA), was applied to the cultures. To this end, organotypic cultures of porcine retinas were cultured and treated with different doses of NMDA (0 [control], 50, 100 and 200μM) on day 2 for 48 hours. On day 7, the retinas were cryo-conserved for histological, Western blot and quantitative rt-PCR (qrt-PCR) analyses. NMDA treatment was found to significantly increase retinal ganglion cell (RGC) apoptosis in all the treated groups, without a profound RGC loss. In addition, the intrinsic apoptotic pathway was activated in the 50μM and 100μM NMDA groups, whereas induced nitric oxide synthase ( iNOS ) expression was increased in the 200μM group. A slight microglial response was detectable, especially in the 100μM group. NMDA treatment induced apoptosis, oxidative stress and a slight microglia activation. All these effects mimic a chronic slow progressive disease that especially affects RGCs, such as glaucoma. A particular advantage of this model is that mediators that can interact in the very early stages of the onset of RGC death, can be easily detected and potential therapies can be tested.